Analysis and Management of Senayan PLTD Noise Pollution - Efendi, Aco Wahyudi (ECOTAS, 2023)
PLTD activities must pay attention to environmental conditions on the important impacts that occur, specifically regarding the impact of noise that occurs from the operation of the machine. This study's intention is to quantify the degree to which the Senayan 101 MW PLTD's operation has an adverse effect on the neighborhood's noise levels. Constant Noise Type having a broad frequency range. It is advised to install a barrier made of concrete blocks 200 x 200 x 400 with a thickness of 300 mm as high as 6000 mm and a distance of 3000 mm in areas where the noise level is above 70 dB.A. This will help to reduce noise pollution by 20.05 dB.A, bringing the initial noise level down to 68.65 dB. A.